Conhecimento, satisfação e segurança à saúde de usuárias de implante subcutâneo com etonogestrel - Rebouças, Lidiane Nogueira (2015)
Cross-sectional study aimed to conduct a situational diagnosis of the use of etonogestrel subcutaneous implant (Implanon®) in the perspective of knowledge, satisfaction, and safety to the health of female users. The population comprised the female users of Implanon® (n=181) from the 2nd Local Health Coordination of the Ceará State, Brazil, and the census sampling method accounted for 106 individuals. Data collection took place through interviews from March to November 2014. Data analysis occurred through the Statistical Package for Social Sciences (SPSS) software version 20.0, and received descriptive statistics and bivariate analysis (Likelihood Ratio and Chi-square tests), considering statistical significance of differences among proportions p<0.05. Average age of participants was 31.32±6.18 years and average years of education were 11.83±3.74. 77.4% of them reported being married or in stable relationship. Per capita income from “over ¼ to ½ minimum wage” (40.6%) prevailed. Knowledge about Implanon® presented higher proportions in items “does not prevent STD/HIV/AIDS” (95.3%), reversibility (93.4%), efficiency (91.5%), adequate time for changing method (91.5%), and mechanism of action (83.0%). We verified association between knowledge of adequate time for changing Implanon® and municipalities (p=0.016), in which municipalities 1 (28.0%) and 2 (17.6%) showed higher inadequate proportions of knowledge. Regarding reversibility of Implanon® (p=0.051) and the method does not prevent STD/HIV/AIDS (p=0.030), municipality 1 presented higher proportion of inadequate knowledge, 20.0% and 16.0%, respectively. Years of education influenced knowledge about adequate time for changing method (p=0.015). There was a predominant knowledge about menstrual alterations (72.6%). Municipality and years of education influenced the level of knowledge about systemic changes (p=0.016 and p=0.040, respectively), in which municipality 1 had a higher proportion of ignorance (24.0%) and 80% of users with up to 5 years of study did not have this knowledge. About complications, “lack of knowledge” prevailed in all items, with greater knowledge of profuse bleeding (35.8%) and severe headache (34.0%). Municipality influenced the knowledge of profuse bleeding complications (p=0.012), with municipality 2 presenting greater percentage of ignorance (94.1%); as for infection at the insertion site (p=0.024), municipalities 3, 4 and 1 had the highest percentage of ignorance (97.7%, 96.0% and 90.9%, respectively). Lack of knowledge about severe headache was associated with years of education (p=0.015), with the highest percentages of ignorance among those with fewer years of study. Time of method use did not influence knowledge. Most participants (71.7%) proved to be very satisfied, revealing an association between satisfaction and longer use of Implanon® (p<0.0001). Incisional complications affected 15.1% of participants and had no association with municipality, time of Implanon® use, and years of study (p>0.05). All users demonstrated at least one adverse effect, predominantly amenorrhea (74.5%). Complications affected 27.4% of participants, with special reference to profuse bleeding (17.9%). With relation to health safety, 74.5% of Implanon® users belonged to categories 1 and 2 of the medical eligibility criteria for contraceptive use, 25.5% to category 3, and no one to category 4.